2005
DOI: 10.1007/s00330-004-2554-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of macrophage-related lung diseases

Abstract: Macrophage-related pulmonary diseases are a heterogeneous group of disorders characterized by macrophage accumulation, activation or dysfunction. These conditions include smoking-related interstitial lung diseases, metabolic disorders such as Niemann-Pick or Gaucher disease, and rare primary lung tumors. High-resolution computed tomography abnormalities include pulmonary ground-glass opacification secondary to infiltration by macrophages, centrilobular nodules or interlobular septal thickening reflecting perib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 124 publications
1
26
0
2
Order By: Relevance
“…However, Marten et al [26] reported that the coexistence of CLE with NSIP patients provided evidence for smoking as a pathogenetic factor in a subset of NSIP patients. Longitudinal studies both in the development of CLE and NSIP have demonstrated that CLE replaces macrophage-related respiratory bronchiolitis [27,28] and that macrophage accumulation of DIP may recede leaving residual fibrotic NSIP [26,29] . In a more recent study, Antoniou et al [30] reported coarser fibrosis and notable honeycombing in smokers with IPF and rheumatoid lung relative to non-smoking counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…However, Marten et al [26] reported that the coexistence of CLE with NSIP patients provided evidence for smoking as a pathogenetic factor in a subset of NSIP patients. Longitudinal studies both in the development of CLE and NSIP have demonstrated that CLE replaces macrophage-related respiratory bronchiolitis [27,28] and that macrophage accumulation of DIP may recede leaving residual fibrotic NSIP [26,29] . In a more recent study, Antoniou et al [30] reported coarser fibrosis and notable honeycombing in smokers with IPF and rheumatoid lung relative to non-smoking counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation leads to radiological improvement and even complete recovery in early cellular and nodular cases of PLCH [89,91,92]. The disease may improve with smoking cessation alone; the 5-and 10-yr survival rate is 74.6% and 63.9%, respectively [93].…”
Section: Plchmentioning
confidence: 99%
“…The mainstay of treatment in patients with DIP consists of corticosteroid therapy, which may cause stabilisation or improvement of the disease. Complete recovery of the disease has been described [59,89]. In ,25% of patients, however, progression of disease may be observed despite steroid therapy [11,59,89] and lung transplantation may be an option.…”
Section: Diagnosis Of Plchmentioning
confidence: 99%
See 2 more Smart Citations